Density Functional Theory-Assisted Synthesis of Self-Curing Epoxy–Acrylic Resin - Yang, Bowen; An, Qiufeng (Frontiers in Chemistry, 2021)
With density functional theory (DFT) as the theoretical guide, the radical reaction index ( ), which is the quantum chemistry reaction index of the reacting monomer in the basic state is obtained through computer calculation. The synthesis of self-curing epoxy acrylate (EMPA) is assisted by the specific numerical values of . Through the physical appearance of EMPA, mechanical properties after curing, and thermal stability, the reliability of the free radical reaction index ( ) assisted synthesis of EMPA is confirmed. The special functional groups of the resin were characterized by Fourier infrared to prove the rationality of the reaction. The cross-sectional morphology characteristics of the resin cured was observed by the field emission scanning electron microscope (SEM). The results show that the closer the molar ratio of the monomers in the reaction to the ratio of the reacting monomers, the better the performance.